Unwavering - Kiland, Taylor Baldwin 1966- (Permuted Press, 2023)
The true story of the women who waged an epic home front battle to ensure our nation leaves no man behind. When some of America’s military men are captured or go missing during the Vietnam War, a small group of military wives become their champions. Never had families taken on diplomatic roles during wartime, nor had the fate of our POWs and missing men been a nationwide concern. In cinematic detail, authors Taylor Baldwin Kiland and Judy Silverstein Gray plunge you directly into the political maneuvering the women navigated, onto the international stage they shared with world leaders, and through the landmark legacy they created. --
Keywords: USA -- Army; Geschichte; Vietnamkrieg; Vermisster; Soldat; Kriegsgefangener; Diplomatie; Ehefrau; Heimatfront; Vietnam War, 1961-1975 / Prisoners and prisons; Vietnam War, 1961-1975 / Missing in action; Military spouses / United States / History / 20th century; Families of military personnel / United States / History / 20th century; Families of prisoners of war / United States / History / 20th century; Prisoners of war / United States / History / 20th century; Ex-prisoners of war / United States / History / 20th century; United States / Foreign relations / 21st century; Guerre du Viêt-nam, 1961-1975 / Prisonniers et prisons; Guerre du Viêt-nam, 1961-1975 / Disparus au combat; Militaires / Conjoints / États-Unis / Histoire / 20e siècle; Familles de militaires / États-Unis / Histoire / 20e siècle; Familles de prisonniers de guerre / États-Unis / Histoire / 20e siècle; Ex-prisonniers de guerre / États-Unis / Histoire / 20e siècle; États-Unis / Relations extérieures / 21e siècle; Diplomatic relations; Ex-prisoners of war; Families of military personnel; Families of prisoners of war; Military spouses; Missing in action; Prisoners of war; United States / https://id.oclc.org/worldcat/entity/E39PBJtxgQXMWqmjMjjwXRHgrq; 1900-2099; History